Presynaptic control of nociceptor signalling: Differential influence of Mu Opioid and GABAergic Systems - Ruth C Riley; Jodie A Trafton; Allan I Basbaum (Pain Research and Management)
The relative contribution of pre- and postsynaptic controls to the flow of nociceptive information at the level of the spinal cord has been one of Ron Melzack's longstanding interests and a key issue in the formulation of the gate control theory. The authors review their own studies, in which they monitored internalization of the neurokinin-1 receptor to examine specifically the action of two classically inhibitory systems - mu opioid and gamma-amino butyric acid (GABA) - on noxious stimulus-evoked tachykinin signalling in the rat spinal cord. Evidence that opioids and GABAergic controls operate differently on the central consequences of any noxious stimulus-induced substance P release is provided. Whereas at least 80% of the tachykinin signalling remained intact after even the highest concentration of spinal morphine or D-Ala2, NMe-phe4, Glyol5-enkephalin administration, spinal administration of the GABAB receptor agonist baclofen had a dramatic inhibitory effect. These findings are discussed in light of the disappointing clinical utility of baclofen and neurokinin-1 receptor antagonists to combat pain.